Conception Rate Evaluation of Three Different Breeds’s Recipients of Bovine Embryos in High Tropical Lands - Farfan-Rojas, Oscar Orlando; Porras-Vargas, José Luis (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The present study was conducted to evaluate the reproductive efficiency on heifers pregnancy rates from three different breeds, as embryo recipients. In the Cundiboyacense highlands, there has been few studies designed to determine which breeds beside, suitable for the environment, are the ones that can provide the best pregnancy rates, as embryo transfer recipients. The results were studied by descriptive statistical analysis using Excel and Minitab (Chi square x2 ) programs, with quantitative variables. The selection of recipients was based on the quality of the corpus luteum, CC normal reproductive tract, between 2 and 3 on a scale from 1 (very weak) to 5 (fat). The embryo transfer was performed by a non-surgically method: The pregnancy rates found were: for Normando Breed of 63%, Holstein, 55.5% and 44.4% for Brangus. The protocol used was Ovsynch, and the transferred embryos were frozen and thawed at the time of transfer.